MASLAHAT DALAM PERSPEKTIF AL-QUR`AN DAN SUNNAH - Abbas, Abbas (DIKTUM: Jurnal Syariah dan Hukum, 2015)
There are three main discussions in this article, namely: the nature of beneficiaries, beneficiaries concept in Al-Qur’an and Hadist explanation. Basically, beneficiaries related to human interests. The beneficiaries are something which is regarded by the common sense because of the good and avoiding damage to humans. When a clash between some benefits occurs, it is something that is a matter of high priority is the beneficiaries. In the Qur’an and Sunnah, there are a lot of information about the purpose and wisdom establishment of syara’ law either globally or in detail.